MINIMASI PENURUNAN DEFECT PADA PRODUK MEBLE BERBASIS PROLYPROPYLENE UNTUK MENINGKATKAN KUALITAS Study Kasus : PT. Polymindo Permata - Yusuf, Muhammad; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
This research is to analyze the optimization of improving the quality of PP-based furniture products. The purpose of this study is to reduce the defect of PP-based meble products. The total level of product defects that occurred reached 16.90% of the production produced during one year. Thus the company has not experienced an optimal point so that Six Sigma analysis needs to be done with efforts to reduce defective products and find the cause of the problem of disability and find solutions with methods or assistive devices so that the percentage of defective products can be reduced to the smallest possible level and achieve company targets This quality improvement can be improved. solve with the Six Sigma method through the stages of Define, Measure, Analyze, Improve. The value of sigma level before improvement is 12.77%. This shows that the company has not implemented the production process properly. After implementing the improvements, the sigma level value is 0.50%. And the ANOVA test results showed a significant difference before making improvements and after being repaired with a mean value of 0.50.